Anatomical characteristics of maxillary sinus septa visualized by cone beam computed tomography. Issue 3 (March 2019) - Hungerbühler, A.; Rostetter, C.; Lübbers, H.-T.; Rücker, M.; Stadlinger, B.
Abstract: Proper implant positioning in the posterior region of the edentulous maxilla commonly requires sinus floor elevation. Maxillary sinus septa increase the risk of membrane perforation during sinus floor elevation. The purpose of this retrospective, cone beam computed tomography (CBCT)-based study was to examine the frequency, number, location, and orientation of antral septa in the maxillary sinus. Further, possible associated factors were assessed. Measurements were performed on CBCT scans of 301 patients (602 sinuses). The data were analysed statistically with respect to patient age, sex, and dentition type. One or more septa were detected in 117 patients (38.9%). A total of 188 septa were found in the 602 sinuses (31.2%). Septa were most often coronally oriented (53.2%), followed by sagittal (24.5%) and transverse (22.3%) orientations. Septa were most often found in the region of the first and second molar (37.2%), followed by the posterior region of the third molar (33.0%) and the anterior region of the premolars and canines (29.8%). A significant association was found between edentulism and the presence of septa. For edentulous patients, the septa were most often transversally oriented. Maxillary sinus septa are encountered in every third patient. This may have an influence on the performance of sinus floor elevation.